Association of the serum uric acid to creatinine ratio with metabolic syndrome in the middle age and older population in China - Zhong, Danrong; Liu, Dongchen; Guo, Yongtian; Huang, Haoyin; Li, Lu; Wu, Fangqin; Huang, Suli (Frontiers in Endocrinology, 2022)
Background Metabolic syndrome (MetS) has attracted great interest, with an increasing prevalence. Recent studies have shown that the serum uric acid-to-creatinine ratio (SUACr) might be an excellent biomarker for MetS risk prediction in diabetic patients and postmenopausal women. However, the relationship between SUACr and MetS in a middle-aged and older population remains unclear. Methods A total of 1277 participants were included in this cross-sectional study. Logistic regression modelling was performed to assess the association between SUACr and MetS in the total population. The dose–response relationship of SUACr and MetS was further assessed by a restricted cubic spline model (RCS). Furthermore, to explore the relationships between the levels of SUACr and the number of metabolic components, analysis of covariance (ANCOVA) was applied. Results The levels of SUACr were lower in the non-MetS participants (OR 1.60, 95% CI 1.36 to 1.89; P<0.001),. Positive and dose–response relationships were further confirmed by the RCS model. We also found that, with increased number of components, the SUACr tended to increase. Moreover, values of SUACr were strongly related to levels of triglycerides (TGs), body mass index (BMI), blood glucose levels, systolic blood pressure/diastolic blood pressure (SBP/DBP), and hypertension. In addition, the positive association between SUACr and MetS also occurred in those patients with normal uric acid levels. Conclusion Elevated values of SUACr were strongly associated with an increased risk of MetS; this positive relationship remained in those individuals with normal uric acid levels.